2009
DOI: 10.4049/jimmunol.0803965
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Capsid Structure Drives CD4-Dependent CD8+ T Cell Response to Vector Encoded Proteins

Abstract: The immunological sequelae of adeno-associated virus (AAV)-mediated gene transfer in vivo is quite complex. In murine models, most AAV capsids are associated with minimal or dysfunctional T cell responses to antigenic transgene products. In this study we compared T cell activation against AAV2/8 and AAV2/rh32.33 vectors expressing nuclear-targeted LacZ (nLacZ), GFP, or firefly luciferase in murine skeletal muscle. We show that, unlike AAV8, AAVrh32.33 yields qualitatively and quantitatively robust T cell respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 65 publications
4
86
0
1
Order By: Relevance
“…Studies in C57BL/6 mice demonstrate that intramuscular gene transfer with AAVrh32.33 vectors induces a robust adaptive immune response toward both capsid and transgene antigen, heavy cellular infiltrate, and a loss of detectable transgene expression at days 35 and 60 after administration (18). To evaluate the role of TLR9 signaling in the induction of this adaptive immune response and transgene loss, WT and Tlr9-deficient mice were i.m.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in C57BL/6 mice demonstrate that intramuscular gene transfer with AAVrh32.33 vectors induces a robust adaptive immune response toward both capsid and transgene antigen, heavy cellular infiltrate, and a loss of detectable transgene expression at days 35 and 60 after administration (18). To evaluate the role of TLR9 signaling in the induction of this adaptive immune response and transgene loss, WT and Tlr9-deficient mice were i.m.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy CD4 + and CD8 + cellular infiltrate has been observed in WT C57BL/6 mice following AAVrh32.33 intramuscular vector transduction (18). To determine the requirement for TLR9 signaling in the induction of this extensive infiltrate, WT and Tlr9-KO muscle cryosections were stained with anti-CD4 and anti-CD8 Abs and examined by fluorescent microscopy at 35 and 60 days after vector administration ( Figure 3A).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…124 Recently, several laboratories compared the immunity of AAV-8 to that of other AAV serotypes (AAV-1, 2, and 5 and rh32.33). 124,131,[135][136][137][138][139][140] Interestingly, all these studies suggest that AAV-8 is less immunogenic. Future mechanistic studies may reveal the molecular underpinning of the unique immune privilege demonstrated by AAV-8.…”
Section: Cellular Immune Response To Aav-mediated Gene Transfer In Thmentioning
confidence: 99%